MODEL PEMBELAJARAN DAN BERSOSIALISASI MAHASISWI BERCADAR DI KAMPUS (Learning and Socializing Models of Wearing Niqab Students at University) - irsyadunnas irsyadunnas; Sri Sumarni; Nora Saiva Jannana (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2021)
In recent years the use of veils in Indonesia is quite attractive, especially by students. The veil culture has become a new trend in how students are dressed on many campuses. In this context, various negative stigmas arise along with the trend of wearing the veil in various environments, including the campus environment, such as: radical and exclusive. Generally, in various state campuses in Indonesia, the use of veil is considered as something that is not standard because it is not in accordance with the culture of Indonesian society. In the Islamic Religious Higher Education environment, the issue was increasingly raised because it was linked to the issue of radicalism, including the case of UIN Sunan Kalijaga who had issued a letter about the guidance of veiled students, even though the letter was eventually revoked. Similarly, the case of IAIN Bukitinggi urged lecturers and students not to wear the veil in the campus environment. The aim of this research is to find out the meaning of niqab for students who are wearing niqab and the way they are socialize with the community. The method used is a qualitative research method with phenomenological approach. Data collection is through interviews, observations, and documentation. This research found that the meaning of niqab for them is self-preservation, self-improvement, and self-avoidance from slander. While in social life, they try to bring themselves well when dealing with community members so that they also get a good response from community members.